The relationship between host behavior and environmental sanitation with the incidence of diarrhea in toddlers - Kirana, Tharisya Ayu (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Diarrhea is a disease transmitted through water and is a major problem in developing countries, including Indonesia. This study aims to determine the relationship between host behavior and environmental sanitation with the incidence of diarrhea in toddlers in the working area of the Makrayu Health Center, Palembang City. Methods: This quantitative research uses a cross-sectional design with a total sample of 68 toddlers. Data analysis was performed univariately, bivariate using chi-square and multivariate multiple logistic regression prediction models. Findings: Based on data from the Makrayu Community Health Center, Palembang City, 2022, the prevalence of diarrhea in toddlers is 28.9%. The results of the multivariate analysis showed that the most significant variable on the incidence of diarrhea in children under five was the habit of washing hands (p-value 0.012) after controlling for the variables of processing, provision, and serving of food, quality of latrines, and waste disposal facilities. Host behavior and poor environmental sanitation can cause rapid transmission of diarrhea. Therefore, people are advised to pay attention to small things with big meanings by always practicing a clean and healthy life to avoid germs that cause disease. Conclusion: The analysis results show a relationship between the incidence of diarrhea in toddlers and food processing, provision and serving, hand washing habits, and garbage disposal facilities. In contrast, the source of clean water, latrines' quality, and garbage disposal have no significant relationship with the incidence of diarrhea in toddlers in the work area. Makrayu Health Center Palembang City. Novelty/Originality of this article: This study uniquely identifies handwashing behavior as the most influential factor in toddler diarrhea incidence after controlling for key environmental sanitation variables.